Memory-based meso-scale modeling of Covid-19 - Kergaßner, Andreas; Burkhardt, Christian; Lippold, Dorothee; Kergaßner, Matthias; Pflug, Lukas; Budday, Dominik; Steinmann, Paul; Budday, Silvia (Computational Mechanics, 2020)
The COVID-19 pandemic has lead to an unprecedented world-wide effort to gather data, model, and understand the viral spread. Entire societies and economies are desperate to recover and get back to normality. However, to this end accurate models are of essence that capture both the viral spread and the courses of disease in space and time at reasonable resolution. Here, we combine a spatially resolved county-level infection model for Germany with a memory-based integro-differential approach capable of directly including medical data on the course of disease, which is not possible when using traditional SIR-type models. We calibrate our model with data on cumulative detected infections and deaths from the Robert-Koch Institute and demonstrate how the model can be used to obtain county- or even city-level estimates on the number of new infections, hospitality rates and demands of intensive care units. We believe that the present work may help guide decision makers to locally fine-tune their expedient response to potential new outbreaks in the near future.<br

Spatiotemporal modeling of first and second wave outbreak dynamics of COVID‐19 in Germany - Lippold, Dorothee; Kergaßner, Andreas; Burkhardt, Christian; Kergaßner, Matthias; Loos, Jonas; Nistler, Sarah; Steinmann, Paul; Budday, Dominik; Budday, Silvia (Biomechanics and Modeling in Mechanobiology, 2021)
The COVID-19 pandemic has kept the world in suspense for the past year. In most federal countries such as Germany, locally varying conditions demand for state- or county-level decisions to adapt to the disease dynamics. However, this requires a deep understanding of the mesoscale outbreak dynamics between microscale agent models and macroscale global models. Here, we use a reparameterized SIQRD network model that accounts for local political decisions to predict the spatiotemporal evolution of the pandemic in Germany at county resolution. Our optimized model reproduces state-wise cumulative infec- tions and deaths as reported by the Robert Koch Institute and predicts the development for individual counties at convincing accuracy during both waves in spring and fall of 2020. We demonstrate the dominating effect of local infection seeds and identify effective measures to attenuate the rapid spread. Our model has great potential to support decision makers on a state and community politics level to individually strategize their best way forward during the months to come.
Keywords: COVID-19 · SIQRD model · Mesoscale outbreak dynamics · Germany